Image, Object and Art: The Photography of Guido Boggiani - Reyero, Alejandra (2012)
This piece reflects upon the use of Guido Boggiani’s photographs among the Chamacoco or Ishir people of the Paraguay Chaco between 1890 and 1900. The study parts from a hermeneutic appreciation of the existent historical material on the subject, including Alfred Gell’s agential approach concerning social issues and Michael Taussig’s understanding of the mimetic nature of photography. The study ends with a discussion about Boggiani’s photographs today and their current circulation among different art venues.